Characterization of rapid cycling bipolar patients presenting with major depressive episode within the BRIDGE‐II‐MIX study. (8th October 2020) - Antonietta Furio, Maria; Popovic, Dina; Vieta, Eduard; Stukalin, Yelena; Hagin, Michal; Torrent, Carla; Azorin, Jean‐Michel; Angst, Jules; Bowden, Charles L.; Mosolov, Sergey; Young, Allan H.; Perugi, Giulio; et al.
Abstract: Objectives: The "Bipolar Disorders: Improving Diagnosis, Guidance, and Education" (BRIDGE‐II‐Mix) study aimed to estimate the frequency of mixed states in patients with a major depressive episode (MDE) according to different definitions and to compare their clinical validity, looking into specific features such as rapid cycling (RC). Methods: Psychiatric symptoms, socio‐demographic, and clinical variables were collected from a sample of 2811 MDE patients, of which 726 (25.8%) were diagnosed with bipolar disorder (BD). The characteristics of bipolar patients with RC (BD‐RC) and without (BD‐NRC) RC were compared. Results: Of 726 BD patients, 159 (21.9%) met DSM‐5 criteria for RC. BD‐RC group presented a higher number of lifetime depressive episodes ( p  < 0.001) with shorter duration of depressive episodes, and more psychiatric comorbidities, as well as higher rates of atypical features ( p  = 0.016) and concomitant (hypo)manic symptoms (irritable mood ( p  = 0.001); risky behavior ( p  = 0.005); impulsivity ( p  = 0.006); and psychomotor agitation ( p  = 0.029)). Patients with RC had a worse functioning ( p  = 0.033), more obesity ( p  = 0.003), and were significantly more likely to be treated with three or more drugs ( p  = 0.007). Conclusions: Important clinical differences between bipolar patients with and without a RC include more depressive morbidity, higher incidence of anxiety disorders, addiction, bulimia, and borderline personality disorder, as well as atypical features during depression and symptoms such as irritability, risky behavior, impulsivity, and agitation. RC patients had poorer functioning than patients without RC, more obesity, and had to be treated with more drugs.